Limits on The Implementation of Contrario Actus Principle in The Procurement of Civil Servants - Risang Pujiyanto; Sonny Taufan; Netti Iriyanti (Universitas Kuningan, 2018)
Procurement of Civil Servants (PNS) which is not in accordance with the legislations and the general principles of good governance have the potential to become State Administration disputes. One of the examples is a civil servant procurement dispute in Dompu District in 2014 where the Judges decided to reject the plaintiffs claim by considering the Contrario Actus Principle. This research was a normative research by using a statute and case approach. The legal materials used in this research were primary and secondary legal materials. Moreover, the data analysis method used was descriptive qualitative. The results showed that in the Civil Servant Procurement Dispute in Dompu District in 2014, the Judges of Mataram Administrative Court judged that the Dompu District Head, in terms of authority and procedure, did not violate the laws and the general principles of good governance. Moreover, in terms of substance, the Judges considered that the Dompu District Heads decision was in accordance with the Contrario Actus Principle. By looking at the decidende ratio and Law Number 30 of 2014 concerning Government Administration, the limits on the implementation of the Contrario Actus principle in the procurement of Civil Servants are; 1) The withdrawn KTUN is a bound KTUN, 2) The withdrawn KTUN has a defective authority, 3) The withdrawn KTUN has a defective procedure, and/or 4) The withdrawn KTUN has a defective substance which is caused by fraud, coercion, bribe, or error.Pengadaan Pegawai Negeri Sipil (PNS) yang tidak sesuai dengan peraturan perundang-undangan dan Asas-Asas Umum Pemerintahan Yang Baik berpotensi menjadi sengketa Tata Usaha Negara. Salah satu contohnya adalah sengketa pengadaan PNS di Kabupaten Dompu Tahun 2014 dimana Majelis Hakim memutuskan menolak gugatan penggugat dengan pertimbangan Asas Contrario Actus. Penelitian ini merupakan penelitian normatif dengan menggunakan pendekatan undang-undang dan pendekatan kasus. Bahan hukum yang digunakan adalah bahan hukum dan bahan hukum sekunder. Metode analisis data yang digunakan adalah deskriptif kualitatif. Hasil penelitian menunjukkan bahwa dalam sengketa Tata Usaha Negara pengadaan PNS Kabupaten Dompu Tahun 2014, Majelis Hakim PTUN Mataram menilai secara kewenangan dan prosedur Bupati Dompu selaku tergugat tidak melanggar peraturan-perundang-undangan dan Asas-Asas Umum Pemerintahan Yang Baik. Sementara secara substansi, Majelis Hakim menilai keputusan Bupati Dompu sudah sesuai dengan Asas Contrario Actus. Dengan melihat ratio decidende dan ketentuan Undang-Undang Nomor No. 30 Tahun 2014 Tentang Administrasi Pemerintahan maka batasan penggunaan asas Contrario Actus dalam pengadaan PNS adalah 1) KTUN yang dicabut merupakan KTUN yang bersifat terikat, 2) KTUN yang dicabut terdapat cacat wewenang, 3) KTUN yang dicabut terdapat cacat prosedur, dan/atau 4) KTUN yang dicabut terdapat cacat